2022
DOI: 10.3389/fmicb.2022.899150
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Phenomic Investigations Reveal Elements in Biofilm Repression and Formation in the Cyanobacterium Synechococcus elongatus PCC 7942

Abstract: Biofilm formation by photosynthetic organisms is a complex behavior that serves multiple functions in the environment. Biofilm formation in the unicellular cyanobacterium Synechococcus elongatus PCC 7942 is regulated in part by a set of small secreted proteins that promotes biofilm formation and a self-suppression mechanism that prevents their expression. Little is known about the regulatory and structural components of the biofilms in PCC 7942, or response to the suppressor signal(s). We performed transcripto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…A recent study showed that the inactivation of the gene Synpcc7942_1510, which encodes a homolog of the Sigma F factor known as SigF1, results in biofilm development [21]. Briefly, a pooled barcoded transposon library, RB-TnSeq, was grown, biofilms were formed, and sequencing of the barcodes indicated the abundance of each mutant in both the biofilm and the planktonic fractions.…”
Section: Inactivation Of Sigf1 Results In Biofilm Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent study showed that the inactivation of the gene Synpcc7942_1510, which encodes a homolog of the Sigma F factor known as SigF1, results in biofilm development [21]. Briefly, a pooled barcoded transposon library, RB-TnSeq, was grown, biofilms were formed, and sequencing of the barcodes indicated the abundance of each mutant in both the biofilm and the planktonic fractions.…”
Section: Inactivation Of Sigf1 Results In Biofilm Developmentmentioning
confidence: 99%
“…This action subsequently leads to the repression of genes that promote biofilm formation, which in turn represses biofilm-promoting genes (Fig. 8, top panel, thick T-bar; [21][22][23][24][25]). Therefore, sigF1-inactivation, which abrogates pili formation, alleviates a major repression pathway, most likely due to disruption of the inhibitor(s) secretion process.…”
Section: Exoproteome Analyses Reveal Substantially Higher Level Of Eb...mentioning
confidence: 99%
See 2 more Smart Citations
“…Random barcode transposon site sequencing (RB-TnSeq) is a methodology that has proven to be particularly useful for elucidating genes that are most important to sustain a variety of conditions and processes in the model cyanobacterium Synechococcus elongatus PCC 7942 ( 9 12 ). In this study we leveraged RB-TnSeq to elucidate the gene set that is most critical in S. elongatus for tolerating UVR stress under a light cycle that resembles natural UVR dosage and short-wavelength spectral quality.…”
mentioning
confidence: 99%